'DANCING TO DEBATE' IN ENHANCING STUDENTS' SPEAKING SKILL: STUDENTS' EXPERIENCES - Hz, Benni Ichsanda Rahman; Pulungan, Anni Holila (Journal of English Education and Linguistics, 2024)
This study is aimed to investigate the utilization of the "Dancing to Debate" method in speaking class from the viewpoint of students. A total of 46 students from the English Education Department at a state university in North Sumatera Province, Indonesia, participated in filling out a questionnaire consisting of 10 Likert scale questions (1 to 5), as well as semi-structured interviews with the students. The qualitative data were collected through a qualitative case study approach to examine a phenomenon within its real-life context. The results show that a significant percentage of students felt that this method helped them feel more confident in speaking English (34.78% strongly agreed, 32.61% agreed). Most students also found the method to be effective in improving their speaking skills (32.61% strong agreed, 28.26% agreed) and making speaking practice more enjoyable (36.96% strongly agree, 45.65% agreed). The positive feedback from students suggests that the strategy was successful in achieving its intended goals and was valued for its positive impact on the learning experience. Overall, the findings of this study align with the importance of making English learning activities enjoyable, fun, and stimulating for children.